Swallowing characteristics in Down syndrome at an advanced age: a preclinical study in the Ts65Dn mouse model - Ostadi, Marziyeh; Fisher, Erin H.; Yu, Y. Eugene; Connor, Nadine P.; Glass, Tiffany J. (Frontiers in Neurology, 2026)
Down syndrome (DS) occurs in approximately one in 800 births worldwide and is associated with various medical complications including swallowing impairments and dysphagia. Advances in childhood survival have led to an increased number of people with DS reaching older ages. Aging is generally accompanied by changes in sensory and motor functions, including those involved in swallowing. Swallowing impairments can lead to complications such as malnutrition, dehydration, and aspiration pneumonia. Despite the multifactorial nature of swallowing impairments in older people with DS, research in this area remains limited, with most studies focusing on pediatric populations. We hypothesized that aged Ts65Dn mice (mouse model of DS; 14 males, 15 females) would demonstrate significant impairments in swallowing performance on quantitative measures derived from videofluoroscopic swallow studies, relative to age-matched euploid controls (genetically typical mice; 14 males and 15 females). Statistical analyses included two-way ANOVA for genotype and sex effects. The Ts65Dn group exhibited significantly lower swallow rates, longer inter-swallow intervals (ISI), increased jaw cycle: swallow ratios (JSR), and lower jaw excursion rates (JER) than euploid controls. Body weight was significantly lower in the Ts65Dn group. These findings confirm persistent swallowing impairments in aged Ts65Dn mice, supporting their use as a model for studying swallowing mechanisms, provide critical insights into swallowing impairments in aging DS and support the need for specialized clinical interventions for swallowing disorders in this population.